Pumping laser excited spins through MgO barriers. (9th March 2017) - Martens, Ulrike; Walowski, Jakob; Schumann, Thomas; Mansurova, Maria; Boehnke, Alexander; Huebner, Torsten; Reiss, Günter; Thomas, Andy; Münzenberg, Markus
Abstract: We present a study of the tunnel magneto-Seebeck (TMS)4 effect in MgO based magnetic tunnel junctions (MTJs). The electrodes consist of CoFeB with in-plane magnetic anisotropy. The temperature gradients which generate a voltage across the MTJs layer stack are created using laser heating. Using this method, the temperature can be controlled on the micrometer length scale: here, we investigate, how both, the TMS voltage and the TMS effect, depend on the size, position and intensity of the applied laser spot. For this study, a large variety of different temperature distributions was created across the junction. We recorded 2D maps of voltages generated by heating in dependence of the laser spot position and the corresponding calculated TMS values. The voltages change in value and sign, from large positive values when heating the MTJ directly in the centre to small values when heating the junction on the edges and even small negative values when heating the sample away from the junction. Those zero crossings lead to very high calculated TMS ratios. Our systematic analysis shows, that the distribution of the temperature gradient is essential, to achieve high voltage signals and reasonable resulting TMS ratios. Furthermore, artefacts on the edges produce misleading results, but also open up further possibilities of more complex heating scenarios for spincaloritronics in spintronic devices.